2001
DOI: 10.2169/internalmedicine.40.382
|View full text |Cite
|
Sign up to set email alerts
|

Cholangiocarcinoma with a Background of Hepatitis B Virus-associated Cirrhosis.

Abstract: Recently, hepatitis virus-associated chronic hepatitis or cirrhosis has been suggested to be involved in the pathogenesis of cholangiocarcinoma (CC). A 52-year-old manwas diagnosed as CCwith a background of hepatitis B virus (HBV)-dependent cirrhosis. A minute hepatic tumor was found during the follow-up, and was diagnosed as CC on percutaneous biopsy. The patient died of hepatic failure and an autopsy revealed the tumor to be a well to moderately differentiated adenocarcinoma. An immunohistological analysis o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…Our findings are consistent with the results reported by a few non‐Chinese studies that have evaluated the role of HBV infection and cirrhosis in the development of ICC (18, 19, 26–30). Taking these studies into account, there seems to be reasonable epidemiological evidence for a causal relationship between HBV and ICC.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are consistent with the results reported by a few non‐Chinese studies that have evaluated the role of HBV infection and cirrhosis in the development of ICC (18, 19, 26–30). Taking these studies into account, there seems to be reasonable epidemiological evidence for a causal relationship between HBV and ICC.…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, one of the persons with occult HBV had a partial hepatectomy for cholangiocarcinoma. While HBV is more tightly linked to the development of HCC, there are several reports of HBV DNA and protein detected in cholangiocarcinoma [20][21][22]. These studies consist of case series or case reports, so the true prevalence of occult HBV in this setting is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, identification of other risk factors is important. Infection with HBV or HCV has been suggested as a potential risk factor for CC [19,20]. A prospective cohort study from Japan showed that 2.3% of 600 patients with HCV-related cirrhosis developed ICC during a mean follow-up of 7.2 years.…”
Section: Discussionmentioning
confidence: 99%